2015
DOI: 10.23937/2378-3656/1410044
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating the Adverse Effects of Zolpidem in a Patient with Alcohol Dependence and SSRI use

Abstract: patients with liver or kidney pathology, resulting in the possibility of increased serum levels and subsequent toxicity [3]. In malnourished patients, hypoalbuminemia is common and can result in elevation of unbound drug concentration that may account for, or contribute to, zolpidem toxicity [5]. Others susceptible to toxicity are women, whose zolpidem plasma levels were noted to be 40% higher than men at equivalent doses, and those with concomitant selective serotonin reuptake inhibitor (SSRI) treatment which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Innamuri et al discussed the management complexities of zolpidem dependence in 2023 [17]. Chopra et al highlighted the amplified adverse effects of zolpidem because of concurrent alcohol and SSRI use [18]. Mattoo, Gaur, and Das addressed zolpidem withdrawal delirium in 2011 [19], and Chate et al reported on zolpidem-induced delirium in 2013 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Innamuri et al discussed the management complexities of zolpidem dependence in 2023 [17]. Chopra et al highlighted the amplified adverse effects of zolpidem because of concurrent alcohol and SSRI use [18]. Mattoo, Gaur, and Das addressed zolpidem withdrawal delirium in 2011 [19], and Chate et al reported on zolpidem-induced delirium in 2013 [20].…”
Section: Discussionmentioning
confidence: 99%